Characteristics of some synthetic terpenoids with a grapefruit odour discovered by serendipity. (25th September 2014) - Bonikowski, Radosław; Świtakowska, Paulina; Jabłońska, Aneta; Kula, Józef; Sienkiewicz, Monika; Gabrysiak, Justyna; Kajrukszto, Krzysztof
ABSTRACT This work presents odour characteristics of a newly synthesized family of seven terpenoid alcohols with citrusy grapefruit odours. The alcohols were prepared from citronellal that was subjected to a two‐ or three‐step reaction sequence to deliver secondary or tertiary alcohols. Two other compounds with an acetal structure (containing 18 and 19 carbon atoms) with the same odour type and very high tenacity were synthesized from (+)‐3‐carene. The most olfactorily potent compounds were 5, 9‐dimethyldec‐8‐en‐2‐ol 10 and 2‐carene derivative acetal 25. Copyright © 2014 John Wiley & Sons, Ltd.